O Teorema de Euler para poliedros e a topologia dos grafos no ensino básico - FREITAS, Janderson dos Santos de (2017)
The paper presents problem solving using Graph Theory and Euler’s Theorem. The research performs specific activities in high school involving graphs in various applications of the Euler relation as a problem solving method with Graph Theory. The relationship of Euler is presented in a Geometric view and by the graphs planning. The research proposes a link between the students ’daily problems with the modeling of problem situations by the Graph Theory, specifically the planar graphs solved with the implementation of Euler’ s Theorem focused on the teaching of basic mathematics. Applications of Graph Theory are shown in solving problems with the bridges of the city of Barra do Corda and the students’ school life.